Blood Chemistry Monitor in use - Photolab (1970)
The instrument, probably Model BCM-400, is consulted by a man taking notes in the foreground. In the background, three other men perform surgery on an animal.
Keywords: Scientific apparatus and instruments; Veterinary medicine; Blood--Analysis; Beckman Instruments, Inc.; Veterinary medicine--Equipment and supplies